A Brief History of Time: From the Big Bang to Black Holes - Hawking, Stephen; Stephen Hawking (London, United Kingdom Bantam Books, 1988)
Stephen Hawking$1 (Bs A Brief History of Time explains groundbreaking ideas about the origin, structure, and eventual fate of the universe. Written in accessible language, it delves into scientific theories related to space, time, black holes, and the nature of the cosmos, making complicated physics understandable to the general reader.s
Updated edition of the international bestseller that explores complex concepts of cosmology including black holes, the Big Bang, and the nature of time.
Keywords: A Brief History of Time: From the Big Bang to Black Holes